2018
DOI: 10.1007/s13197-018-3451-0
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant capacity and UPLC–PDA ESI–MS polyphenolic profile of Citrus aurantium extracts obtained by ultrasound assisted extraction

Abstract: This study aimed to evaluate different pretreatments and solvent ratios on the total phenolic content and antioxidant activity of Citrus aurantium (sour orange) peel extracted by ultrasound. A two-factor (2 9 3) factorial design was implemented, with fresh and dry peels as pretreatment conditions, and water (100%), 50% aqueous ethanol (v/v) and 96% aqueous ethanol (v/v) as the solvents. The phenolic compounds were identified and quantified by ultra-performance liquid chromatographyphotodiode array and electros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 35 publications
(45 reference statements)
1
9
0
Order By: Relevance
“…According to our previous work [46], where a phenolic extract of Citrus aurantium was partially purified, a synergic effect of phenolic compounds was suggested after the higher antioxidant activity found in the crude extract in comparison with the purified fractions at a specific TPC. These results were also reported by Shiraishi et al, [47] who evaluated the antioxidant activity of the phenolic compounds in table grapes.…”
Section: Changes Of Tpc During the Drying Process In Lemon Residue Flmentioning
confidence: 96%
“…According to our previous work [46], where a phenolic extract of Citrus aurantium was partially purified, a synergic effect of phenolic compounds was suggested after the higher antioxidant activity found in the crude extract in comparison with the purified fractions at a specific TPC. These results were also reported by Shiraishi et al, [47] who evaluated the antioxidant activity of the phenolic compounds in table grapes.…”
Section: Changes Of Tpc During the Drying Process In Lemon Residue Flmentioning
confidence: 96%
“…The synergistic effect of the two eco-enzymes increases the potency of their antimicrobial activity against a wide range of bacteria [21]. The high content of polyphenolic compounds and flavonoids in pineapple and orange peel extracts are found to be responsible for their excellent antimicrobial and antioxidant activities [22,23]. Bromelain from pineapple extracts is shown to be effective in killing Enterococcus faecalis by disrupting the peptidoglycan and polysaccharide components of bacterial cell membranes [24].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the valorization of this type of waste is an attractive approach that could offer useful alternatives through the production of value-added chemicals, fuels, and advanced carbon materials [ 1 , 3 ]. In particular, in Mexico, an average of 4.2 million metric ton of citrus is produced per year, from which 90% is dedicated to fresh consumption and 10% is used in the juice and concentrates industry, generating a high amount of waste, where 40−60% of citrus becomes waste, including peels, seeds, and membranes [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among other varieties of citrus fruits, sour orange ( Citrus aurantium ) is less used for fresh consumption due to its sourness; instead, sour orange juice is often used as an ingredient in meat marinades or salad dressings. For the Citrus sinensis variety, current research has shown that sour orange peel (SOP) can be used as a source of added value compounds such as essential oils, pectin, phenolic compounds, and flavonoids, as well as flavoring and acidifying agents for food [ 5 , 7 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%